Toxoplasma gondii among captive wild mammals in zoos in Brazil and Cuba: seroprevalence and associated risk factors - Villar-echarte, Ginette (2021)
Toxoplasma gondii is a zoonotic parasite of worldwide distribution that can infect several species of homeothermic animals. Few studies have evaluated the exposure of captive wild animals to T. gondii. This study involved a serological survey of anti-T. gondii antibodies in mammals kept in Cuba’s National Zoo (PZN) and in the Rio de Janeiro Zoo (RIOZOO) in Brazil. The study consisted of a total of 231 serum samples from mammals, 108 from PZN and 123 from RIOZOO. All the samples were subjected to IgG anti-T. gondii testing by means of the inhibition ELISA method and the modified agglutination test, respectively. T. gondii antibodies were detected in 85.2% samples from PZN and 32.5% samples from RIOZOO. At the PZN, Perissodactyla (92.3%) was the order with the highest serological prevalence rate, whereas at the RIOZOO, the order Primates (46.7%) stood out (p<0.05). In addition to this association, the origin of the PZN animals was also associated with T. gondii infection. This finding demonstrates the need for constant veterinary monitoring of captive wild mammals in order to link the serological diagnosis with clinical alterations indicative of toxoplasmosis.